EFEKTIVITAS PENGGUNAAN ARANG TEMPURUNG KELAPA, ARANG AMERIKA, ARANG KAYU LABAN DAN ARANG KAYU GALAM TERHADAP PEMURNIAN BIOGAS - Achmad Kusairi Samlawi; Hasan Sajali (Scientific Journal of Mechanical Engineering Kinematika, 2021)
One of the problems contained in biogas is carbon dioxide that can reduce the burning calorific value of biogas. It is necessary to purify. This research aims to reduce the levels of carbon dioxide in the biogas. This research was conduct with passing biogas from sanitary landfills to biogas purification insulators containing charcoal adsorption media. After the adsorption process, the biogas is continued and collected in the tube until the pressure reaches 2 bar and then tested the carbon dioxide level bypassing biogas to the chamber for carbon dioxide reading using CO2 analyzer. The result of reduction of carbon dioxide from biogas testing without purification was 13955,03 ppm and after purified by coconut shell charcoal decreased to 8713,78 ppm with effectivity purification equal to 37,56% and density of 0,688 gr/cm3, with American Charcoal decreased to 7399,41 ppm with the effectiveness of purification by 46.98% and density of 0,817 gr/cm3, with laban wood charcoal decreased to 11310.07 ppm with the effectiveness of purification of 18.95% and density of 0,448 gr/cm3 and with Glam wood charcoal decreased to 12867.84 ppm with the effectiveness of purification of 7.79% and density of 0,446 gr/cm3. So that the effectiveness of purification of the highest biogas is by using American Charcoal with the absorption of 46,98% and has the highest density value of 0,817 gr/cm3, for the magnitude value of charcoal density is directly proportional to the magnitude absorption of carbon dioxide and also related with the magnitude surface area, where the higher the surface area then, the greater the adsorption capacity to carbon dioxide.